Student satisfaction in Higher Education: an analysis from the Agronomy course at Instituto Federal Goiano (Research, Society and Development, 2020)
This study aimed to assess satisfaction perceived by students of the agronomy course on two campuses at the Federal Institute Goiano in relation to their own course. The identification of the main components of the General Satisfaction of students was made based on previous studies. The data were collected by applying questionnaires to 149 students of the agronomy course and analyzed using statistical techniques Hierarchical Cluster Analysis and Multiple Linear Regression, to establish in a non-parametric way, since the constructs did not present normal distribution, which of the studied constructs represent the general satisfaction of the students. The results showed that Teacher Involvement and Interaction between Teacher and Student are the determining constructs for the general satisfaction of the student, demonstrating in this study that the role of the teacher is of great importance in the feeling of satisfaction on the part of the student of the agronomy course.